2016
DOI: 10.1051/0004-6361/201527201
|View full text |Cite
|
Sign up to set email alerts
|

A reddening-free method to estimate the56Ni mass of Type Ia supernovae

Abstract: The increase in the number of Type Ia supernovae (SNe Ia) has demonstrated that the population shows greater diversity than has been assumed in the past. The reasons (e.g. parent population, explosion mechanism) for this diversity remain largely unknown. We investigated a sample of SNe Ia near-infrared light curves and correlated the phase of the second maximum with the bolometric peak luminosity. The peak bolometric luminosity is related to the time of the second maximum (relative to the B light curve maximu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 64 publications
(101 reference statements)
5
21
0
Order By: Relevance
“…They inferred that the diversity in t2 values of SNIa is driven by different masses of 56 Ni produced in the explosion. As a follow-up, Dhawan et al (2016) identified a strong correlation between the peak bolometric luminosity (Lmax) and t2 for a sample of SNIa with well-measured NIR data. Since the luminosity at peak corresponds to the instantaneous energy deposition rate from 56 Ni decay (known as " Arnett's Rule" Arnett 1982), the authors used the correlation between Lmax and t2 and Arnett's rule to infer a 56 Ni mass distribution.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They inferred that the diversity in t2 values of SNIa is driven by different masses of 56 Ni produced in the explosion. As a follow-up, Dhawan et al (2016) identified a strong correlation between the peak bolometric luminosity (Lmax) and t2 for a sample of SNIa with well-measured NIR data. Since the luminosity at peak corresponds to the instantaneous energy deposition rate from 56 Ni decay (known as " Arnett's Rule" Arnett 1982), the authors used the correlation between Lmax and t2 and Arnett's rule to infer a 56 Ni mass distribution.…”
Section: Discussionmentioning
confidence: 66%
“…Kasen (2006), based on radiative transfer calculations of synthetic lightcurves, predicted that t2 is a function of the 56 Ni mass produced by the SNIa. Indeed, Dhawan et al (2016) found a strong correlation between the peak bolometric luminosity (and therefore, 56 Ni mass, see Arnett 1982) and t2 for a sample of SNIa with low-extinction from host galaxy dust. They demonstrate that this parameter can be used to infer the 56 Ni mass for SNIa.…”
Section: Introductionmentioning
confidence: 97%
“…The impact of this on further parameter estimation is discussed below. Assuming Arnett's rule is obeyed and a rise time of t R =19 days with an error of 3 days (Stritzinger et al 2006;Dhawan et al 2016), we can derive a M56 Ni from the computed value of L max :…”
Section: Bolometric Propertiesmentioning
confidence: 99%
“…These observations have been critical to derive global parameters for SNe Ia, e.g. synthesized 56 Ni mass, total ejecta mass (Stritzinger et al 2006;Scalzo et al 2014;Dhawan et al 2016Dhawan et al , 2017. However, there is a wealth of information available in observations shortly after explosion as well as at late times (∼ a year after maximum, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging of the supernova reveals the presence of clear echoes (Yang et al 2017). Estimates of the 56 Ni mass using the timing of the NIR second maximum (Dhawan et al 2016) and γ-ray observations (Churazov et al 2015) infer masses of 0.64 ± 0.13 M and 0.62 ± 0.13 M , respectively, consistent with the estimate for a normal SN Ia (Stritzinger et al 2006;Scalzo et al 2014). Optical spectra of SN 2014J in the nebular phase are remarkably similar to the 'normal' SNe 2011fe and 2012cg (Amanullah et al 2015).…”
Section: Introductionmentioning
confidence: 99%